1991
DOI: 10.1007/bf00010728
|View full text |Cite
|
Sign up to set email alerts
|

The aluminium signal: New dimensions to mechanisms of aluminium tolerance

Abstract: The physiological basis of plant reaction to and tolerance of aluminium (AI) is poorly understood. We review the results of investigations into A1 toxicity and root physiology to develop a theoretical basis for explaining the reaction of the root to AI, including suggested roles for Ca 2+, mucilaginous cap secretions and endogenous growth regulators in mediating a transmitted response between Al-damaged cap cells and the interacting cell populations of the cap and root.This information is used to identify poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 102 publications
1
40
0
3
Order By: Relevance
“…Both the Ca chelator EGTA (ethyleneglycol-bis-(aminomethylether)A^,A^,A'^',A'^'-tetraacetic acid; Bennet & Bandu, 1989) and Al (Bennet, Breen & Fey, 1985) disrupt the secretory function of the peripheral cap cells. Bennet & Breen (1991) suggested that these observations were consistent with a primary response to Al occurring through competition between Al and Ca for sites external to the plasmalemma. Calcium chelating agents, such as EDTA and EGTA, have been shown to inhibit root hair formation (Cormack, 1959(2, b;Jaunin & Hofer, 1988), suggesting a comparable disruption in the function of Ca.…”
Section: Dj Brady and Otherssupporting
confidence: 61%
“…Both the Ca chelator EGTA (ethyleneglycol-bis-(aminomethylether)A^,A^,A'^',A'^'-tetraacetic acid; Bennet & Bandu, 1989) and Al (Bennet, Breen & Fey, 1985) disrupt the secretory function of the peripheral cap cells. Bennet & Breen (1991) suggested that these observations were consistent with a primary response to Al occurring through competition between Al and Ca for sites external to the plasmalemma. Calcium chelating agents, such as EDTA and EGTA, have been shown to inhibit root hair formation (Cormack, 1959(2, b;Jaunin & Hofer, 1988), suggesting a comparable disruption in the function of Ca.…”
Section: Dj Brady and Otherssupporting
confidence: 61%
“…When Al is selectively applied to the elongation zone or to all of the root except the apex, growth is unaffected (Ryan et al, 1993). Bennet and Breen (1991) described a number of changes to the ultrastructure of cap cells in maize roots after a 2-h treatment with Al and suggested that Al might inhibit root growth indirectly, via a signal-response pathway involving the root cap, hormones, and secondary messengers. This was an attractive hypothesis and consistent with the known involvement of the root cap in signal perception and hormone distribution.…”
Section: Root Apices Are a Target For Al Toxicitymentioning
confidence: 99%
“…In roots, one of the primary sites of Al toxicity is the meristems (4,8,9,13). Thus, if the differential Al sensitivity among wheat cultivars is due to a differential Al accumulation in the meristems, then the meristematic tissue of a sensitive cultivar will accumulate more Al than the tissue of a tolerant cultivar.…”
mentioning
confidence: 99%